The Sami and the Inupiat : finding common grounds in a new world - Nyborg, Kristine (Universitetet i Tromsø, 2010)
This thesis is about the meeting of two indigenous cultures, the Sami and the Inupiat, on the Alaskan tundra more than a hundred years ago. The Sami were brought over by the U.S. government to train the Inupiat in reindeer herding. It is about their adjustment to each other and to the rapidly modernizing world they found themselves a part of, until the term indigenous became a part of everyday speech forty years ago. During this process they gained new identities while holding on to their indigenous ones, keeping a close tie to nature along the way. The thesis is based on a four-month fieldwork in Alaska during the summer of 2009, and is the second part of a Masters project. The first part is a film, Sami footprints in Alaska, which explores how the reindeer has affected the Native Alaskan more than a hundred years after the Reindeer Project of the 1890s.